ANALISIS PRODUKTIVITAS GAS HIDROGEN BERDASARKAN ARUS DAN TEGANGAN PADA PROSES ELEKTROLISIS H2O - Fitriyanti, Fitriyanti (JFT : Jurnal Fisika dan Terapannya, 2019)
This study designed a HHO generator by separating oxygen (O2) and Hydrogen (H2) gas. The controlled variable is the HHO generator container made of plastic with a width of 12 cm, length 24 cm, height 20 cm in the shape of a rectangle, and filled with aquades as much as 1 litter, the distance between the electrodes is 1.5 mm, the temperature that occurs during the electrolysis process is 33oC to 40oC. The research variables observed were current and voltage used during the H2O electrolysis process, Brown's gas flow rate in the measuring cup (ml / min), the efficiency of the HHO generator, ie the energy or power used in the H2O electrolysis process Based on the research results obtained by the addition of a PWM Controller to increase the voltage can increase the productivity of the hydrogen gas produced. The value of the power needed affects the effectiveness of the electrolysis device, the greater the power needed, the effectiveness will decrease, this is influenced by the increasing amount of electricity consumption required in the operation of the tool. The maximum effectiveness obtained is 8,127% with 36 watts of power.